Jihad in the life of Prophet Muhammad: a mercy or terror - Osmani, Noor Mohammad (IIUM Press, 2011)
A global concern about Islam has been raised along with some pertinent events in the last few decades. Eventually, the occurrences of 9/11, Middle East issue, Iraq, Afghanistan and other countries have ignited this interest to a great extent among the masses around the globe. Many Western orientalists project a distorted image of Islamic Jihad, and advocate that, though Muhammad (PBUH) offered some ethical policies regarding warfare and conflict, he failed to maintain an ideal stance in many of the events of war in his lifetime instead. This issue bears a great significance as they attempt to link those historical instances with present day terrorist activities in the name of Islam and allegedly by some deviated Muslim terrorists, who accept no moral guilt for killing innocent civilians and destroying civil infrastructures. However, the historians have described that the Prophet Muhammad (PBUH) participated in 27 military expeditions whereas most of them achieved their goals without armed confrontation except for nine times. Besides, he sent a good number of military missions for various purposes and places. In response to propaganda campaigns by mass media and different scholarly activities, the importance of an objective analysis of the concept of Jihad from the perspective of the Qur’an and the authentic Sunnah is apparent. The objective of this research is to study the life of the Messenger of Allah (PBUH) in order to develop an objective response to the Orientalist criticisms regarding Jihad. This study would critically deal with some controversial issues in Jihad and analyze them based on the authentic historical references from the life of the Prophet. The ultimate findings of this study would be expected to clarify the reality against some biased misinterpretation of the events from the life of the Messenger of Allah (PBUH), who was the ambassador of peace and mercy to all humanity in all circumstances, ages and places.